2020
DOI: 10.1515/jpem-2020-0113
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between breastfeeding and obesity in high school girls

Abstract: ObjectivesSome factors in infancy can play a role in the development of adolescent obesity. Understanding these factors can help prevent early complications in adolescents associated with obesity in adulthood. The aim of this study was to determine the prevalence of overweight and obesity among high school girls in Khorramabad and its relationship with breastfeeding history.MethodsThis was a cross-sectional study. This study was conducted in 832 high school girls during the academic year 2016–2017. Samples wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…After excluding duplicates, 17,871 titles were examined, and after excluding those studies that were clearly irrelevant, 269 abstracts were reviewed, and 58 19–76 new studies were identified in the update of the systematic review (Figure 1). The meta‐analysis comprised 169 estimates on the association of breastfeeding with overweight or obesity, drawn from 159 studies including 58 that were published since our previous review (Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…After excluding duplicates, 17,871 titles were examined, and after excluding those studies that were clearly irrelevant, 269 abstracts were reviewed, and 58 19–76 new studies were identified in the update of the systematic review (Figure 1). The meta‐analysis comprised 169 estimates on the association of breastfeeding with overweight or obesity, drawn from 159 studies including 58 that were published since our previous review (Table S1).…”
Section: Resultsmentioning
confidence: 99%